Species Diversity of Bumblebees (Hymenoptera: Apidae) from Different Mountain Regions of Kashmir Himalayas (Journal of Scientific Research, 2011)
The species diversity of bumblebees was investigated in three provinces Jammu, Kashmir and Ladakh during 2007-2010. Bumblebee queens, workers and males were collected right from the commencement till to the end of flowering stage in all the three mountain regions. In total, 27 species of bumblebees were collected and identified, of which eleven species were common in the two regions, e.g., Kashmir and Ladakh. A list of species assemblages and abundance is provided in each of the mountain ranges. Species diversity of three regions was determined with Shannon-Weiner diversity index and evenness was calculated with indices of Pielou. The obtained results showed species diversity; evenness and species richness were more observable in Kashmir compared with Ladakh and Jammu. The three sample sites within the Kashmir Himalayas indicate significant differences in species diversity; the Kashmir region had higher species diversity and richness than the other regions. Most species of bumblebees were collected in altitudinal ranges of 3000-4000m. Four species viz. Bombus cornutus, B. parthenius, B. miniatus and B. morawitizianus are recorded for the first time from this region, while B. morawitizianus turn out to be the first record to the national list.Key words: Species Diversity; Bumblebees; Kashmir Himalayas.© 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v4i1.8815J. Sci. Res. 4 (1), 263-272 (2012)